Assessment of Sustainable Natural Tourism Objects in Coastal Areas: A Case Study of The Mangrove Trail Natural Tourism Attraction in Darunu Village, North Minahasa - Jongky W.A. Kamagi; Pearl L. Wenas; , Frans V. Rattu; Youdy Gumolili; Margresye D. Rompas (Sam Ratulangi University, 2025)
categories are sustainable, fairly sustainable, and unsustainable. The weights used are very important, important, moderate, less important, and unimportant. The scores used are 30, 25, 20, 15, and 10. The weightings were based on the assessment of experts with expertise in the tourism field. These tourism experts include academics, NGO workers in the tourism sector, tourism practitioners such as tour guides, and government employees from the Tourism Office at district, city, or provincial levels. This study defined five dimensions: environment (weighted 5), economy (weighted 5), social (weighted 4), governance/institutions (weighted 4), and infrastructure, communication, and promotion (weighted 5). The environmental dimension received a score of 525, categorizing it as sustainable. The economic dimension, received a score of 500, categorizing it as fairly sustainable. The social dimension received a score of 380, categorizing it as sustainable. The governance/institutional dimension received a score of 460, categorizing it as sustainable. The infrastructure, communication, and promotion dimension received a score of 750, categorizing it as sustainable. Almost all dimensions of the Darunu Village mangrove trail are considered sustainable, except for the economic dimension, which is considered quite sustainable. Keywords: Sustainable, tourist attraction, ADO-ODTWA, mangrove trail, Darunu Abstrak Penilaian ini dilakukan dengan mengikuti cara penilaian ADO-ODTWA. Kategori penilaian adalah berkelanjutan, cukup berkelanjutan dan tidak berkelanjutan.Bobot yang digunakan adalah sangat penting, penting, moderat, kurang penting dan tidak penting.Nilai yang digunakan adalah 30,25,20,15 dan 10. Penilaian bobot menggunakan penilaian pakar yang menguasai bidang kepariwisataan. Ahli bidang pariwisata ini meliputi: akademisi, pekerja LSM/NGO di bidang pariwisata, praktisi dibidang pariwisata seperti tour guide, pegawai pemerintahan instansi Dinas Pariwisata di kabupaten, kotamadya ataupun propinsi. Dalam penelitian ini ditetapkan 5 dimensi yaitu: Lingkungan (bobot 5), ekonomi (bobot 5), sosial (bobot 4), tata Kelola/kelembagaan (bobot 4) serta infrastruktur, komunikasi dan promosi (bobot 5). Dimensi lingkungan mendapatkan skor 525 sehingga mendapatkan kategori berkelanjutan. Dimensi ekonomi mendapatkan skor 500 dengan kategori cukup berkelanjutan. Dimensi social mendapatkan skor 380 dengan kategori berkelanjutan. Untuk dimensi tata Kelola/kelembagaan mendapatkan nilai 460 dengan kategori berkelanjutan. Serta dimensi infrastruktur, komunikasi dan promosi mendapatkan nilai 750 dengan kategori berkelanjutan.Hampir semua dimensi penilaian mangrove trail desa Darunu berkelanjutan kecuali dimensi ekonomi yang cukup berkelanjutan Kata kunci : Berkelanjutan, objek wisata, ADO-ODTWA, mangrove trail, Darunu